Weekly high‐dose liposomal amphotericin B prevents invasive aspergillosis after heart transplantation. Issue 6 (26th October 2021) - Cointault, Olivier; Joly, Marine; Cassaing, Sophie; Labaste, François; Danet, Chloé; Porte, Lydie; Guitard, Joelle; Kamar, Nassim; Faguer, Stanislas
Abstract: Background: Preventive strategies for invasive aspergillosis (IA) have still not been determined in heart transplant recipients whereas IA leads to a high mortality rate at 12 months posttransplantation. The use of voriconazole or echinocandins was proposed but can favor emergence of Aspergillus or Candida sp . resistant strains or promote neurological and liver disorders in some patients. Objectives: To assess whether universal prophylaxis with weekly high‐dose of liposomal amphotericin‐B (L‐AmB) can safely prevent IA in heart transplant recipients. Patients/methods: Retrospective before/after study that included 142 patients who received heart transplantation between 2010 and 2019 at the University Hospital of Toulouse (France). Weekly high dose of L‐AmB (7.5 mg/kg/week) was used as universal prophylaxis from 2016 because of high environmental exposure to Aspergillus sp . and high incidence of IA. Results: Cumulative 1‐year incidence of IA decreased from 23% to 5% after introduction of L‐Amb prophylaxis. Multivariate analysis (Cox model) identified L‐AmB prophylaxis as a protective factor against IA (hazard ratio [HR] 0.21 [95% confidence interval 0; 0.92], p = .04), whereas postoperative renal replacement therapy was associated with IA (HR 3.6 [95% confidence interval 1.38; 9.3], p = .001), after correction for confounding effects (induction regimen, methylprednisolone pulses and history of hematological malignancy). The incidence of acute kidney injury requiring renal replacement therapy was similar in the two groups, suggesting a low risk of kidney toxicity when L‐AmB is used weekly. No patient developed severe kidney electrolyte loss nor L‐AmB‐related anaphylaxis. Conclusions: Once‐weekly high‐dose L‐AmB is safe and may prevent the development of IA after heart transplantation.